ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBIAYAAN BERBASIS BAGI HASIL (Studi empiris pada Bank Umum Syariah (BUS) dengan periode pengamatan mulai tahun 2012-2014) - Annisa Soffat (AKT 16 UMY 049, 2016)
classified into two categories, namely conventional banks and banks with Islamic principles. The importance of the function and role of Islamic banking in Indonesia, the Islamic banks need to improve its performance in order to create banks with Islamic principles of healthy and efficient. Profitability as a reference in measuring the profits to be so important to know whether the company has been running its business efficiently. Based on this it can be formulated an issue is whether FDR effect on the financing for the results, whether NPF effect on the financing for the results, whether the CAR affect the financing for the results, whether TBH affect the financing for the results. The aim of the study was to analyze the effect of FDR to finance for the results, analyze the effect of NPF to finance for the results, analyze the influence of CAR to finance for the results, and analyze the effect of TBH to finance for results. The number of population in this study is the Islamic Banks (BUS) in the year 2012 to 2014, the sample can be used as many as 10 Islamic banks. Samples were taken by purposive sampling method where the sample selection on the characteristics of the population that is already known. Then analysis of the data obtained. Analysis of the data used in this study is the classical assumption test, multiple regression analysis, and test hipotesis.Untuk analyze data using SPSS software tools. From the results of hypothesis testing Financing to Deposit Ratio (FDR) significantly affects the financing based on the results, the Non Performing Financing (NPF) a significant negative effect on the financing based on the results, the Capital Adequacy Ratio (CAR) negatively affect based financing for the results, and Sharing level (TBH) positive and significant impact on financing berbasi for results. Keywords: FDR, NPF, CAR, TBH, Financing